A Sonata de Deus e o diabolus: nacionalismo, música e o pensamento social no cinema de Glauber Rocha - Siqueira, André Ricardo [UNESP] (2014)
The aim of this work is to analyze the cultural nationalism in Brazil and its reflection in three major productions of filmmaker Glauber Rocha in the 1960s: Black God, White Devil (1964), Entranced Earth (1967) and Antônio das Mortes (1969). We analyze how the music raises points of intersection between nationalism derived from the modern art week 1922 and the concept of conservative modernization. The musical language is used as a prime tool of analysis in relation to time perception and the modal and tonal languages, as well as in pairs, rural and urban, modern and archaic, classical and popular. In another key, nationalism present in these films also reflects the thinking of Mário de Andrade on popular culture and the role of the intellectual in relation to this culture, incorporated by Glauber and questioned in these three films.